2009
DOI: 10.1007/s10815-009-9314-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of in vitro oocyte maturation with lectin supplementation and expression analysis of Cx43, GDF-9, FGF-4 and Fibronectin mRNA transcripts in Buffalo (Bubalus bubalis)

Abstract: Mitogenic lectin supplemented maturation media improves oocyte quality for in vitro embryo production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…For this reason, an oocyte has more gap junction channels than other cells and may be influenced more by adjacent cells. Recent studies regarding oocyte maturation have focused on the role of gap junctions and their main component protein Cx43 (Pant et al ., 2005; Pandey et al ., 2009; Kempisty et al ., 2014). Compared with normal cells, which have no zona pellucidae, oocytes have transzonal projections through zona pellucidae (Palma et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, an oocyte has more gap junction channels than other cells and may be influenced more by adjacent cells. Recent studies regarding oocyte maturation have focused on the role of gap junctions and their main component protein Cx43 (Pant et al ., 2005; Pandey et al ., 2009; Kempisty et al ., 2014). Compared with normal cells, which have no zona pellucidae, oocytes have transzonal projections through zona pellucidae (Palma et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They are implicated in integrin-mediated cell adhesion, assembly of the extracellular matrix, and multi-modular protein structures [ 41 ]. It has been reported that Fibronectin affects cumulus expansion and polar body extrusion [ 42 ], so it regulates cell adhesion and plays a role in oocyte maturation. Plasminogen (PLG) and Kininogen-1 were the other two proteins with high degrees that were down-regulated and up-regulated in PCOS patients, respectively [ 41 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in recent years have shown significant expression of connexin 43 (Cx43) during both oocyte (50) and granulosa cells (30,31) in vitro primary culture. This protein (GJA1, gap junction associated protein, alpha 1, also known as Cx43) turns out to be the main constituent in the connections between individual GCs populations: mural-mural and mural-CCs (68).…”
Section: Role Of Connexins Gene Family In Reproductive Systems Processesmentioning
confidence: 99%